Russia vs. EU: Confrontation in a Contested Neighbourhood. A Challenge to the Helsinki Accords - Marsili, M. (Europe as a Global Actor (EGA2021), 2021)
The Helsinki Final Act of 1975, that concluded the first Conference on Security and Cooperation in Europe, reaffirmed the fundamental principle of renouncing the threat or use of force against the territorial integrity or political independence of any state. Through this agreement, the Soviet Union gained the implicit recognition of the ‘sphere of influence’ that was determined in Eastern Europe after the end of World War II. After the collapse of the Soviet Union, a series of conflicts arose between the Russian Federation and its neighbors, some of which are members of the European Union or participate in the European Neighbourhood Policy. Some of these conflicts were fought at the kinetic level, some other through the resort to hybrid warfare, a blend of traditional and irregular tactics that makes overt and covert use of a wide range of tools: military and civilian, conventional and unconventional, including information and influence operations. This paper aims to investigate the hybrid warfare strategy carried out by the Russian Federation in the confrontation with the European Union to regain dominance in its contested neighbourhood: the Baltic states (Estonia, Latvia, and Lithuania), Ukraine (Crimea and Donbass, i.e. Donetsk and Luhansk People's Republics), Georgia (South Ossetia and Abkhazia) and Moldova (Transnistria).